Lexical Density in Reader’s Digest Magazine - Sari, Andara Ninggar; Ekawati, Rosyida (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2021)
This study concerns with the use of lexical density in Reader’s Digest Magazine. This study used quantitative method. In collecting data, the writer used the document method. The source of data of this research is the lexical items and grammatical items in Reader’s Digest Magazine. In analyzing the data, the writer used lexical density theory by Ure. The source of data of this research is the lexical items and grammatical items in Reader’s Digest Magazine. The result of the lexical density shows there are health article with density around 61, 34%, animal kingdom article with density around 61,56%, languages article with density around 58, 83%, parenting article with density around 54, 68%, and travel article with density around 64, 05%. Keywords: Lexical Density, lexical item, grammatical item, Reader’s Digest